Predict the Accuracy of the Performance of the Serve and Receive Skills in Terms of Methods of Attention to Volleyball for Students - Madlool, Dr. Hala Razzaq (International Journal of Psychosocial Rehabilitation, 2020)
The researchers discussed the distinguished scientific and technological progress in all areas of life, and considering the field of physical education as one of the most prominent areas of human knowledge that is developing and is still developing on the foundations and principles of its scientific research, and the role and importance of each of the methods of attention and its importance accurately performing the skills of sending and receiving volleyball The study objectives to identify: • The level of methods of attention and accuracy of the performance of the serve and receive skills of volleyball students • The strength and direction of the relationship of attention methods precisely to the performance of the transmit and receive skills in volleyball • Detecting the proportions of the contribution methods of attention with accuracy of the serve and receive skills of volleyball students • Predict the accuracy of the serve and receive skills in terms of methods of attention to volleyball for students The researchers adopted the descriptive method in the survey method and correlative and predictive studies to achieve the goals of the research and test its hypothesis. The research community also included students of the second stage in the College of Physical Education and Sports Science University of Karbala for the academic year (2018-2019) and the research sample was chosen by (80) students. Through the results of the results of the statistical analysis of the data and the study of the relationship of variables with each other, conclusions were reached, the most important of which is to identify the relationship of each of the methods of attention accurately to the performance of the serve and receive skills in volleyball and the development of predictive equations for each of the serve and receive skills in terms of the researched variables.